Palliative radiotherapy for leptomeningeal carcinomatosis: analysis of outcome, prognostic factors, and symptom response - El-Shafie, Rami; Kronsteiner, Dorothea; Uzun-Lang, Kristin; Schlaich, Fabian; Adeberg, Sebastian; Paul, Angela; Häfner, Matthias; Katayama, Sonja; Hörner-Rieber, Juliane; Hoegen-Saßmannshausen, Philipp; Löw, Sarah; Debus, Jürgen; et al. (Frontiers in oncology, 2019)
Introduction: The purpose of this article is to report our institution’s ten-year experience on palliative radiotherapy for the treatment of leptomeningeal carcinomatosis (LC), assessing survival, neurologic outcome and prognostic factors. Patients and methods: We retrospectively analyzed 110 patients who received palliative radiotherapy for LC between 2008 and 2018. The most common histologies were breast cancer (n=43, 39.1%) and non-small cell lung cancer (NSCLC) (n=31, 28.2%). Radiotherapy was administered as whole-brain radiotherapy (WBRT) (n=51, 46.4.0%), focal spinal RT (n=11, 10.0%) or both (n=47, 42.7%). 25 patients (22.7%) were selected for craniospinal irradiation. Clinical performance and neurologic function were quantified on the neurologic function scale (NFS) before and in response to therapy. A Cox Proportional Hazards model with univariate and multivariate analysis was fitted for survival. Results: 98 patients (89.1%) died and 12 (10.9%) were alive at the time of analysis. Median OS from LC diagnosis and from the beginning of RT was 13.9 weeks (IQR: 7.1 - 34.0) and 9.9 weeks (IQR: 5.3 - 26.3), respectively. In univariate analysis, prognostic of longer OS were a Karnofsky performance scale index (KPI) of ≥70% (HR 0.20, 95%-CI: [0.13; 0.32], p500 U/l (HR 3.59, 95%-CI: [1.61; 8.01], p=0.002). Clinical performance, symptom response and serum LDH stayed independently prognostic for survival in multivariate analysis. RT was well tolerated and except for grade III myelosuppression in 19 cases (17.3%), no high-grade acute toxicities were observed. Neurologic symptom stabilization was achieved in 83 cases (75.5%) and a sizeable improvement in 39 cases (35.5%). Conclusion: Radiotherapy is a well-tolerated and efficacious means of providing symptom palliation for patients with LC, delaying neurologic deterioration while probably not directly influencing survival. Prognostic factors such as clinical performance, neurologic response and serum LDH can be used for patient stratification to facilitate treatment decisions.